Body water assessment using bioimpedance spectroscopy during rapid weight loss and recovery in Japanese wrestlers - Shiose, K.; Kondo, E.; Sagayama, H.; Yamada, Y.; Osawa, T.; Motonaga, K.; Ohuchi, S.; Kamei, A.; Nakajima, K.; Higaki, Y.; Tanaka, H.; Takahashi, H. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Athletes in weight-category sports conduct rapid weight loss (RWL) followed by weight regain (WR) before competition. Body water assessment during RWL and WR is important for monitoring changes in body composition and for predicting excessive dehydration. Bioimpedance spectroscopy (BIS) is an easy tool for assessing body water status. In contrast to the single-frequency impedance technique, BIS can assess extra- and intra-cellu ar water (ECW and ICW) content, and total body water (TBW) content separately.